Effects of scan speed on vapor plume behavior and spatter generation in laser powder bed fusion additive manufacturing. (December 2018) - Zheng, Hang; Li, Huaixue; Lang, Lihui; Gong, Shuili; Ge, Yulong
Abstract: In-situ observation and metrology of the complex phenomena is a critical step to better understanding of the fundamental physics involved in laser powder bed fusion additive manufacturing process. By using high-speed imaging, we observed and analyzed the vapor plume evolution and spatter generation during single track formation of 304 stainless steel within a board range of scan speed. The experiments were performed on both powder bed and on bare substrate under identical laser parameter sets and observation conditions, in order to identify the role of powder particle on spatter ejection and process stability. With video frames superimposed, observation results are presented and analyzed at track level. It is shown that scan speed has a significant influence on the vapor plume behavior and process stability, and the spatter generation during single track formation is shown to be well related with process stability, rather than with the energy input. Additionally, a unique type of droplet spatter was identified at the starting point of track formation as result of the coupling between the melt pool and intensive vapor flux.